Analisis Prinsip 6C, 7P dan 3R pada Penyaluran Produk Pembiayaan di KSPP Syariah BMT Peta Sidoarjo - Moh Sahhal Jauhari; Siti Khumairo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
People who want to get financing assistance for consumptive activities or productive businesses must meet adequate requirements for prospective debtors of financing products in accordance with the provisions imposed by the institution. This step is taken by management by going through a selection process on prospective debtors in the principles of 6c, 7p and 3r to determine whether the prospective debtor deserves a financing product or not. Financing analysis is an activity that examines important and noteworthy aspects of customers who will be financed by financial institutions. The purpose of financing analysis is to obtain a clear and true picture of the condition of the customer to be financed. Thus, correct and objective recommendations can be given. The approach in this research uses an inductive approach, which studies problems in society and certain situations. Including the processes that take place and the influence of a phenomenon. By using an inductive approach, researchers will describe the data obtained through qualitative methods, namely with interview data, observation and documentation, the type of research used is the type of case study. Providing Financing by KSPPS BMT PETA Sidoarjo, Analyzing the provision of financing using the 6C, 7P and 3R principle financing analysis. 6C analysis includes (Character, Capacity, Capital, Collateral, Condition Of Economy and Constrain). 7P analysis includes (Personality, Party, Purpose, Prospect, Payment, Profitability and Protection). 3R analysis includes Returns Repayment and Risk) of all these principles are all applied by KSPPS BMT PETA Sidoarjo in channeling financing, in accordance with their respective principles, efforts to reduce financing risks. Thus the application can reduce bad debts and increase current financing.